Effects of copper vapor laser irradiation (λ = 510.6 nm) on the enamel and dentine of human teeth: An ultra-structural morphologic study - Niccoli-Filho, Walter [UNESP]; Plácido Penna, Luiz Alberto [UNESP]; Mello Rode, Sigmar [UNESP]; Riva, Rudimar (Mary Ann Liebert, Inc., 2004)
Objective: A morphological and ultra-structural study of copper vapor laser (λ = 510.6 nm) effects on enamel and dentine was performed to show the effects of this radiation. Methods: A total of 15 human molars were cut in half; 15 pieces were separated for irradiation on enamel and 15 for dentine. These two groups were further divided into five experimental groups, including a control group, comprised of three half-sections each, irradiated by a CVL laser with a power of 7 W, a repetition rate of 15,000 pulses/sec and exposed at 500, 600, and 800 msec and 1 sec irradiation times with a 5-sec interval between irradiations. Results: In an ultra-structural SEM exam, we observed that on the enamel surfaces irradiated for 1 sec there was morphological alteration that consisted of catering, flaking, and melting on the surfaces. There was no alteration for the other exposure times. On the dentine teeth irradiated for 1 sec, we observed an evident ultra-structural alteration of melted tissue and loss of morphological characteristics. In the dentine group irradiated by 800 msec, we observed ablation and a partial loss of morphological characteristics. In the dentine groups irradiated by 500 and 600 msec, no alteration was observed. Conclusions: The results showed that irradiation with CVL promoted morphologic changes in the enamel as well as in the dentine and demonstrated a need for future studies in order to establish a safe protocol for further use in the odontological practice.
Keywords: Copper; Dentin; Electron microscopy; Enamel; Human; Laser; Molar tooth; Radiation exposure; Ultrastructure; Controlled study; Copper vapor laser; Human tissue; Mmorphology; Odontology; Radiation dose; Safety; Scanning electron microscopy; Time; Vapor; Copper; Dental Enamel; Dentin; Humans; Lasers; Microscopy, Electron; Molar; Enamels; Morphology; Scanning electron microscopy; Surfaces; Copper vapor laser irradiation; Flaking; Human teeths; Odontology; Laser beam effects